PENERAPAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) MENGGUNAKAN METODE HOT-FIT DI RUMAH SAKIT JIWA ACEH - Apriana, Ana (Jurnal Penelitian Kesmasy, 2024)
This study aims to determine how the application of hospital management information systems (simrs) using the Hot-Fit method in Aceh Mental Hospital. This type of research is quantitative with a cross sectional design. The population in this study amounted to 18 people in the Medical Record Installation and IT. Sampling using Total Sampling technique, data collection was carried out using questionnaires, observation and static tests were carried out with spearman rank tests. The results showed that 18 respondents chose the human factor category as many as 10 people were not good (55.6%) and chose the good category 8 people (44.4%), the category chose the organization factor (organization) was not good as many as 9 people (50.0%) and chose the good category as many as 9 people (50.0%), the category chose the technology factor (technology) was not good as many as 10 people (55.6%) and chose the good category as many as 8 people (44.4%), The category chose the Benefit factor (Net Benefit) less good as many as 9 people (50.0%) and the category chose good 9 people (50.0%) while the category chose the application of the Hospital Management Information System (SIMRS) less good as many as 10 people (55.6%) and chose the good category as many as 8 people (44.4%). The implementation of the hospital management information system (simrs) has not run well, so it is recommended that the hospital always maintain simrs in order to better improve the quality of the system used, the need to improve the quality of human resources by conducting training (workshops) or coaching the use of simrs applications so as to provide quality services so as to make the hospital quality.